Guo, R., Wang, J.M., Zhang, W., He, D., Yu, J. & Yang, D.M. (2022) Pteris pseudoamoena (Pteridaceae), a new species from Guangxi, China and Vietnam. Phytotaxa 550 (3): 215–223. - Guo, Rui; Wang, Jia-Mei; Zhang, Wen; He, Dan; Yu, Jing; Yang, Dong-Mei (Phytotaxa, 2022)
N/A